PENGARUH PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR TEMATIK KELAS V SDN 66 PONTIANAK KOTA - Lestari, Vidia; Halidjah, Siti; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to examine how high the effect of the application of problem based learning to the thematic learning outcomes V in class grade students at SDN 66 Pontianak City. The method used is the experimental method, a form of research Quasi Experimental Design, with the type of Non-Equivalent Control Group Design. The population in this research is all fifth grade students consisting of 73 students. The research sample consisted of class V A as a control class of 37 and V B as an experimental class of 36. The data collection tool is a written test in the form of multiple choice. Based on data analysis, the average post-test results of the experimental class were 72,00 while the average post-test results of the control class were 68,65. The results of the t-test (polled varians) are obtained tcount of 2,757, and ttable (α = 5% (dk = 36 + 37 - 2 = 71) of 1,997. From the results of the calculation of the effect size obtained is 0,53(medium criteria). This means that the application of problem based learning have a good influence on the thematic learning outcomes V in class grade students at SDN 66 Pontianak City. Keywords: Problem Based Learning, Thematic, Learning Outcomes